Potential inhibiting activities of phytochemicals in Scilla natalensis bulbs against schistosomiasis - Oyebamiji, Abel Kolawole; Babalola, Jonathan Oyebamiji; Odelade, Kehinde Abraham; Akintelu, Sunday Adewale; Nubi, Olubunmi Ayoola; Aworinde, Halleluyah Oluwatobi; Faboro, Esther; Akintayo, Emmanuel Temitope; Semire, Banjo (Eclética Química, 2023)
Schistosomiasis remains one of the severe ailments that affect both man and woman in South Africa. It is caused by blood fluke, and the rate at which it causes death is alarming in some areas of America, Asia as well as in African countries. It is a neglected tropical disease (NTD) with grave impact on social and economic situation of countries with low sanitation awareness. Thus, the search for lasting solution to this menace, has drawn the attention of many global researchers using phytochemicals from Scilla natalensis via in silico approach. The studied compounds were optimized using Spartan 14. Docking study was executed via Pymol, Autodock tool, Auto dock vina and discovery studio. Compound 9 with –8.2 kcal mol–1 and –9.4 kcal mol–1 as binding affinity proved to possess highest ability to inhibit glutathione S-transferase and thioredoxin-glutathione reductase than other compounds. Also, ADMET properties for compound 9 and praziquantel were explored and reported. Our findings may open the door for the design of novel drug-like molecules with better efficiency.